176 Intravascular B cell lymphoma: a case series. Issue 3 (9th February 2012) - Kendall, K; Thomas, R H; Lammie, G A; Neal, J W; Corkill, R G; Robertson, N P
Abstract : Intravascular B cell lymphoma is a rare subtype of diffuse large B cell lymphoma. Proliferation of lymphoma cells in small blood vessels causes occlusion. Four cases are presented. Cases 1 (62 years male) and 2 (40 years female) had decreased perianal sensation, leg weakness and faecal incontinence. Case 1 also had increased anal sphincter tone and case 2, urinary retention. Case 3 (69 years male) had urinary retention, constipation and a left leg flaccid monoparesis. All three cases had raised CSF protein (0.62–1.42 g/l) and areas of abnormal increased signal in the deep white matter on MRI. Cases 2 and 3 had abnormal increased signal in the distal thoracic cord: conus on MRI. Cases 2–4 had raised serum lactate dehydrogenase (477–1215 IU/l). At postmortem, atypical B lymphocytes were found in blood vessels of the spinal cords and brains of cases 1–3. Case 4 (49 years male) had a prolonged seizure with postictal agitation. CT head showed two hypodense areas in the right parietal and occipital lobes (Abstract 176 figure 1A ). These had resolved on a later MRI but there was a new left frontal lesion (Abstract 176 figure 1B, C ). He became aggressive with delusions, visual and auditory hallucinations and MRI spectroscopy showed temporal and frontal lobe involvement (Abstract 176 figure 1E–H ). Right temporal pole biopsy showed atypical B lymphocytes within cerebral blood vessels (Abstract 176 figure 2 ). He was treated with CHOP chemotherapy. His hallucinations ceased, his paranoia decreased and a CT head demonstrated lesion resolution.